Growing Points of Southern California - Kuznetsova, D.V. (Економічний вісник Донбасу, 2014)
The aim of this paper is to discuss and show up the main growing points of regional economic system of Southern California. The paper intends to bring together the aimed and contemporary implemented vectors of policy. On the economic side the importance of selected type of area development has played big role in public recognition. Eventually, the established system of polycentricity allows to involve and develop an unlimited number of industries, sectors and actors. It gives the opportunity and impetus for continuous and flexible modeling and fine tuning of sustainable and successful life sustenance. Extensively built cooperation relationships and promising sectors allows California to be and remain a leading regional and global hub. Discussing these processes and the related policy responses might also be interesting for many regions in Central and Eastern Europe, as similar developments might be expected in the future there as well.